FISCAL SERVICES, FISCAL POLICY, AND SOCIAL MEDIA DYNAMICS INFLUENCE ON PROPERTY TAX COMPLIANCE - Muhammad Iqbal; Jenny Erisanthia (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the influence of fiscal services, fiscal policy, and social media dynamics on property tax compliancein Kutai Kartanegara Regency. This is a quantitative research project using primary data measured with a Likert scale. The sample consists of 402 property tax respondents in Kutai Kartanegara Regency, and the data was analized using SmartPLS 4. The results demonstrate that fiscal services, fiscal policy an social media dynamics each have a significant and positive effect on property tax compliance in Kutai Kartanegara Regency.